Some Characterizations of Weighted Holomorphic Function Classes by Univalent Function Classes. (11th March 2021) - Ahmed, A. El-Sayed; Omran, S.
Abstract : Some characterizations of Q K, ω p, q − type classes of holomorphic functions by Schwarzian derivatives with known conformal-type mappings are introduced in the present manuscript. Moreover, the action of the pre-Schwarzian derivatives on Q K, ω p, q − type classes, typically the univalent ones by using concerned Carleson-type measures, is investigated. In addition, we reveal important characterizations of some concerned weighted analytic-type spaces with the known Schwarzian derivatives evolving certain Q − type of concerned function class for a high utility toward practical and feasible application of concerned domains.